(untitled) (Journal of Engineering, 2023)
Rainwater harvesting could be a possible solution to decrease the consequences of water scarcity and energy deficiency in Iraq and the Kurdistan Region of Iraq (KRI). This study aims to calculate the water and energy (electricity) saved by rainwater harvesting for rooftops and green areas in Sulaimani city, KR, Iraq. Various data were acquired from different formal entities in Sulaimani city. Moreover, Google Earth and ArcMap 10.4 software were used for digitizing and calculating the total rooftop and green areas. The results showed that for the used runoff coefficients (0.8 and 0.95), the harvested rainwater volumes were 2901563 and 12197131 m³ during the study period (2005 – 2006) and (2019-2020). Moreover, by comparing the study area’s rainwater harvesting volume and water production, the water-saving percentage was 8.21 to 22.68%. Furthermore, the energy-saving percentage recorded was from 7.70 to 22.5% by implementing rooftop rainwater harvesting. On the other hand, using average daily rainfall data for the year (2005-2020), the total water-saving percentage and the total energy-saving rate for both runoff coefficients were very close. Water and energy-saving results were calculated using year-by-year rainfall data, taking more time and effort for its computation. Moreover, the water-saving percentage for the selected green area was not encouraging, and the results were between 0.73 and 11.15%. Additionally, the storage size for three typical buildings was calculated, and the results show the average storage size required for rainwater harvesting using daily rainfall data was 11.2 to 14.68 m³ (house), 291.42 to 422.33 m³ (school), and 10.5 to 11.41 m³ (hotel) for runoff coefficients of 0.8 and 0.95, respectively.